Blended Learning Using PhET and Props to Improve Students Concept Understanding - Benta, Monika Grasiana; Wiyanto, Wiyanto (Universitas Negeri Semarang, 2024)
This study aims to improve students' understanding of concepts for high school class X on topic of Work and Energy. This research is a quantitative research, a type of experimental research, namely Tru Experimental Design. The research design used pre-post test experiment design. Instruments used in research using assessment of students' concept understanding. The results of the study of concept understanding using the Blended Learning model are 0.69 and Conventional is 0.64 which both use PhET media and teaching aids. Blended Learning is slightly higher. The effectiveness of Problem-Based Learning between Blended Learning classes shows the average result of understanding student concepts is 84.08 and conventional classes show the average result of understanding student concepts is 82.11. The independent t-test analysis was -1.02 and the significant 2-tailed was 0.31, while the 0.05 study alpa showed 0.300.05. Significant results show that Blended Learning classes are more effective than conventional classes.